Screening seven commercial essential herb oils for larvicidal activity against the mosquito Aedes aegypti (Linnaeus), a vector of the dengue virus - Tanawat Chaiphongpachara, Sedthapong Laojun, Wallapa Wassanasompong (Journal of Applied Pharmaceutical Science, 2020)
Mosquitoes are tiny flying insects of great importance as vectors to many pathogenic organisms, including viruses. Aedes aegypti is a primary vector of the dengue virus that causes dengue fever, which is a globally important disease, threatening people in developing countries. In this research, we screened seven commercial herb essential oils, including cassia, cinnamon, East Indian lemongrass, bay, sweet basil, holy basil, and ginger for larvicidal activity against larvae of the dengue virus vector A. aegypti. The results revealed the efficacy of seven commercial pure essential oils against mosquito larvae. The cinnamon oil had the highest larvicidal activity (LC50 = 0.03 ppm and LC90 = 0.04 ppm), followed by cassia, holy basil, bay, sweet basil, East Indian lemongrass, and ginger essential oils. These results are important from the public health perspective since they relate to a dengue vector that requires alternative organic substances for its control and elimination.
Keywords: Essential oils, A. aegypti, larvicidal activity, mosquito larvae, ectoparasite.